Clinical features and predictors of masked uncontrolled hypertension: from Korean ambulatory blood pressure monitoring (Korabp) registry. (25th November 2020) - Lee, Y; Kim, H.J; Shin, J.H; Shin, J; Lim, Y.H; Park, J.K; Heo, R; Park, S; Ihm, S.H; Pyun, W.B
Abstract: Background: Clinical characteristics of patients with masked uncontrolled hypertension (MUCH) are poorly defined, and few studies have reported on clinical predictors of MUCH. We investigated demographic, lifestyle, clinical and blood pressure (BP) characteristics in patients with MUCH and proposed a prediction model for MUCH. Method: We analyzed 2044 subjects taking antihypertensive medication enrolled in the Korean Ambulatory Blood Pressure Monitoring (Kor-ABP) registry, who were categorized into controlled hypertension (n=481, normal office BP, normal 24-hour ABP), pseudo-uncontrolled hypertension (n=131, high office BP, normal 24-hour ABP), MUCH (n=380, normal office BP, high 24-hour ABP), and sustained uncontrolled hypertension (n=1, 052; high office BP and high 24-hour ABP). Result: The prevalence of MUCH increased with office systolic BP (SBP) and diastolic BP (DBP), whereas it was not associated with the numbers of antihypertensive drugs. But in patients with a high office SBP (≥130 mmHg), the prevalence of MUCH increased with decreasing numbers of antihypertensive drugs (interaction p=0.008; Figure 1A). Multiple logistic regression analysis identified high office SBPs and DBPs, prior stroke, dyslipidemia and single anti-hypertensive agent use as independent predictors of MUCH (Table 1). A prediction model using these predictors showed a high diagnostic accuracy (C-index 0.833) and a goodness of fit for the presence of MUCH (Figure 1B). Conclusion: MUCH is associated with the borderline increase in office BP and the underuse of anti-hypertensive drugs as well as dyslipidemia and prior stroke, which underscores the importance of achieving the optimal BP control level in the high risk patients. The proposed model would accurately predict MUCH in patients with controlled office BP. Funding Acknowledgement: Type of funding source: None